A Phenomenology of Difference: Learning from Fanon’s encounter with existential phenomenology (Existential Analysis: Journal of the Society for Existential Analysis, 2024)
For several critics, phenomenology is instituted on universalist views which ignore the historical realities of class, race and gender. They also maintain that phenomenology implies suppression of difference. One of these critics was the political philosopher, psychiatrist and activist Frantz Fanon. Usually associated with Sartre, Fanon was also engaged with Merleau-Ponty’s phenomenology. Drawing on Merleau-Ponty’s and Fanon’s writings, on black and queer studies on the body, nature and exclusion, this paper will focus on aspects of this engagement, including the notions of bodily schema (Merleau-Ponty) and ‘historical-racial schema’ (Fanon). It will outline potential tenets for a phenomenology of difference.
Keywords: Phenomenology; Fanon; Merleau-Ponty; bodily-schema; difference